Analyzing the Implementation of the Inaportnet System for Enhancing Digital Port Services at Soekarno–Hatta Port Makassar - Vera Melinda; Rudianto; Freddy J Rumambi (Jurnal Ilmu Manajemen Profitability, 2026)
The rapid digital transformation of maritime logistics has encouraged ports to adopt integrated information systems to improve efficiency, transparency, and service quality. However, despite the national implementation of port community systems in Indonesia, empirical evidence on how such systems operate at the port level and what factors influence their effectiveness remains limited. This study aimed to analyze the implementation of the Inaportnet system and to identify the supporting and inhibiting factors affecting digital service improvement at Soekarno–Hatta Port in Makassar. The study employed a qualitative descriptive research design. Data were collected from primary and secondary sources through structured interviews, observation, and documentation. The primary informants included port authority staff, a maritime transportation information system coordinator from the Ministry of Transportation, and a shipping agency representative. Data were analyzed using qualitative descriptive techniques and a SWOT framework to evaluate strengths, weaknesses, opportunities, and threats related to the system’s implementation. The findings indicated that the Inaportnet system had been implemented relatively well and contributed to faster and more transparent port services, including document approval processes that could be completed within approximately 30 minutes after submission. The system also improved efficiency through single submission services, electronic data integration, and reduced administrative errors. However, several challenges remained, including occasional network downtime, technical dependence on central system management, and limited digital capabilities among operators of traditional shipping vessels. The study concludes that while Inaportnet significantly enhances digital port services, further improvements in human resource capacity, infrastructure reliability, and stakeholder digital literacy are essential to achieve fully integrated and sustainable maritime digital services.